A Virtual Reality System Associated with Attention Restoration Techniques - Cunha, Ana Laura; Felisbino, Guilherme Perez; Siqueira, Alexandre Gomes de; Kalyanataman, Sriram; Cardoso, Alexandre (Proceedings of the Latin American Congress on Free Software and Open Technologies (Latinoware); 2025: Proceedings of the 22nd Latin American Congress on Free Software and Open Technologies, 2025)
This paper presents the development of a Virtual Reality system focused on exploring immersive experiences aimed at the relaxation and well-being of users exposed to conditions of prolonged stress. The proposal was conceived experimentally, integrating elements such as contemplative environments, soft soundtracks, and future possibilities for breathing techniques, guided meditation, and progressive muscle relaxation in digital environments.The application is described as exploratory, considering contexts of interest such as hemodialysis patients, individuals with chronic pain, or students under high academic pressure, without constituting psychological or therapeutic intervention. Although the current version does not incorporate active artificial intelligence, the system's architecture was planned to allow for future integration with adaptive features capable of personalizing the experience based on user responses. It is emphasized that the system is in the prototype stage and does not yet have integration with commercial virtual reality devices, being currently tested only in a computational environment.